Serum Metabolic Profile in Patients With Long-Covid (PASC) Syndrome: Clinical Implications - Pasini, Evasio; Corsetti, Giovanni; Romano, Claudia; Scarabelli, Tiziano M.; Chen-Scarabelli, Carol; Saravolatz, Louis; Dioguardi, Francesco S. (Frontiers in Medicine, 2021)
Background: Many patients who have been suffering by COVID-19 suffer of long-COVID syndrome, with symptoms of fatigue and muscular weakness that characterize post-acute sequelae SARS-CoV-2 infection (PASC). However, there is limited knowledge about the molecular pathophysiology, and about the serum profile of these patients. Methods: We studied the blood serum profile of 75 selected patients, with previous confirmed COVID-19, two months after hospital discharge, who reported new-onset fatigue, muscle weakness and/or dyspnea not present prior to the virus infection and independently from concomitant diseases and/or clinical conditions. Results: All patients had very high serum concentrations of ferritin and D-Dimer. 87% and 72% of patients had clinically significant low levels of hemoglobin and albumin respectively. 73% had elevations in erythrocyte sedimentation rate and CRP. 27% had elevations in LDH. Conclusions: The co-existence of patient symptoms along with blood markers of coagulation, protein disarrangement and inflammation suggests ongoing alterations in the metabolism, promoting an inflammatory/hypercatabolic state which maintains a vicious circles implicated in the persistence of PASC. The persistence of altered D-Dimer levels raises the possibility of long-term risks of thromboembolic disease. All these markers levels should be accurately evaluated in the long-term follow-up, with individualized consideration for prophylactic nutritional, anti-inflammatory and/or anticoagulant therapy if indicated.